Penerapan Khiyar pada Pengembalian Barang Dalam Transaksi Jual Beli Pakaian Grosir Di Pasar Komplek WTC Jambi - Sari, Ani Mutiara; Pangiuk, Ambok; Baining, Mellya Embun (Indonesian Journal of Islamic Economics and Business, 2022)
This research aims to determine the application of khiyar in the return of goods in buying and selling clothes at the Jambi WTC complex market. This study uses qualitative analysis methods, where primary data is obtained from interviews and secondary data is obtained from documentation. The place in this study is the WTC Jambi shop-house complex market and the actors in this study are traders and buyers in the WTC Jambi shop-house complex market. The results of the study are as follows. (1) The application of khiyar on the return of goods at the Jambi WTC complex market has been carried out even though there is still need for improvement or it is not maximized besides that the majority do not recognize the term "Khiyar". But conceptually they have done it. (2) The implementation of the existing buying and selling contract process carried out by wholesale clothing sellers in the Jambi WTC complex market is still not in accordance with the concept of Islamic business ethics. Because there are still traders who cheat, as at the beginning of their agreement, and there are still traders who only care about their own profits without seeing that one party is being harmed. Of course this is very detrimental to the buyer and this also should not be applied and is not in accordance with Islamic business ethics. (3) The obstacle faced in carrying out khiyar on the return of goods at wholesale clothing at the Jambi WTC complex market is that the term khiyar practice according to Islam is not applied comprehensively. Although in fact they have implemented some provisions in Islam. So there is still a need for improvement by reviewing Islamic rules regarding buying and selling, including khiyar. Lack of socialization from the government in carrying out buying and selling contracts in Islam in discussing khiyar issues and ethics in trading in Islam. Keywords: Khiyar, Buy and Sell,Islamic Bussines Ethic